THE INFLUENCE OF PROFESSIONAL CAPABILITY AND EMPLOYEE EXPERIENCE ON IMPROVING INNOVATIVE BEHAVIOR AND EMPLOYEE PERFORMANCE - Maulana, Indra; Cahyono, Budhi (Universitas Muria Kudus, 2024)
This research investigates the relationship between professional capability and employee experience on innovative behavior and employee performance and the influence of innovative behavior on employee performance. The type of research is explanatory research, which aims to analyze the relationship between exogenous and endogenous variables. This study's population consisted of employees from four different manufacturing companies. This study uses quantitative methods with primary data obtained from questionnaires. The sample selection will use a non-probability sampling method, which is purposive sampling, where not all of the population can be sampled. The sample in this study was 100 employees. Data analysis used the PLS method. The results showed a positive and significant effect on all hypotheses. The limitations of the research are the completion time for collecting data and the lack of direct validation from respondents. For future agendas, research should be carried out in various companies. It could be developed by modification models, confirming relationships between variables, and understanding other indicators of employee performance and innovative behavior in a study.